Effects of ursodeoxycholic acid on the gut microbiome and colorectal adenoma development. (16th January 2019) - Pearson, Talima; Caporaso, J. Gregory; Yellowhair, Monica; Bokulich, Nicholas A.; Padi, Megha; Roe, Denise J.; Wertheim, Betsy C.; Linhart, Mark; Martinez, Jessica A.; Bilagody, Cherae; Hornstra, Heidie; Alberts, David S.; et al.
Abstract: It has been previously reported that ursodeoxycholic acid (UDCA), a therapeutic bile acid, reduced risk for advanced colorectal adenoma in men but not women. Interactions between the gut microbiome and fecal bile acid composition as a factor in colorectal cancer neoplasia have been postulated but evidence is limited to small cohorts and animal studies. Using banked stool samples collected as part of a phase III randomized clinical trial of UDCA for the prevention of colorectal adenomatous polyps, we compared change in the microbiome composition after a 3‐year intervention in a subset of participants randomized to oral UDCA at 8‐10 mg/kg of body weight per day (n = 198) or placebo (n = 203). Study participants randomized to UDCA experienced compositional changes in their microbiome that were statistically more similar to other individuals in the UDCA arm than to those in the placebo arm. This reflected a UDCA‐associated shift in microbial community composition ( P < 0.001), independent of sex, with no evidence of a UDCA effect on microbial richness ( P > 0.05). These UDCA‐associated shifts in microbial community distance metrics from baseline to end‐of‐study were not associated with risk of any or advanced adenoma (all P > 0.05) in men or women. Separate analyses of microbial networks revealed an overrepresentation of Faecalibacterium prausnitzii in the post‐UDCA arm and an inverse relationship between F prausnitzii and Ruminococcus gnavus. In men who received UDCA, the overrepresentation of F prausnitzii and underrepresentation of R gnavus were more prominent in those with no adenoma recurrence at follow‐up compared to men with recurrence. This relationship was not observed in women. Daily UDCA use modestly influences the relative abundance of microbial species in stool and affects the microbial network composition with suggestive evidence for sex‐specific effects of UDCA on stool microbial community composition as a modifier of colorectal adenoma risk. Abstract : It has previously been reported that ursodeoxycholic acid (UDCA), a therapeutic bile acid, reduced risk for developing advanced colorectal adenoma in men but not women. Interactions between the gut microbiome and fecal bile acid composition as a factor in colorectal cancer neoplasia have been postulated but evidence is limited to small cohorts and animal studies. We illustrate small but significant impacts of UDCA on the human gut microbiome.